Using the technique of mating disruption for Cryptoblabes gnidiella (Lepidoptera: Pyralidae) population management on grapevine - Oliveira, José Eudes de Morais; Fernandes, Maria Herlândia de Araújo; Gama, Farah de Castro; Botton, Marcos; Carvalho, Andréa Nunes Moreira de (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the efficiency of mating disruption technique, with the synthetic sex pheromone compound (Z)‑11‑hexadecenal (Z11–16: Ald) at 1.8% and (Z)‑13‑octadecenal (Z13–18: Ald) at 1.8%, for controlling the honeydew moth, Cryptoblabes gnidiella (Lepidoptera: Pyralidae), population in grape (Vitis vinifera) cultivars destined to wine production. The experiments were carried out in two locations in the region of São Francisco Valley, Brazil, in commercial production areas of grapes used for processing, with the cultivars Cabernet Sauvignon, Petit Verdot, Tempranillo, and Chenin Blanc. The evaluated treatments were: mating disruption using Splat (specialized pheromone and lure application technology) releasers, applied at 500 points per hectare (2 g per point); and a control without application. The effect of the technique was evaluated on adults of C. gnidiella using Delta type trap baited with 2 g of synthetic pheromone of the same formulation. The damage on grape clusters was evaluated at harvest. The use of mating disruption technique reduced the capture of adult C. gnidiella in more than 59% in 'Tempranillo', 68% in 'Chenin Blanc', 80% in 'Cabernet Sauvignon', and 97% in 'Petit Verdot'. At harvest, fruit damage was reduced from 65 to 100% in the treated areas. The synthetic sex pheromone is effective in reducing C. gnidiella mating in vineyards, using the mating disruption technique.